Green financing and bank profitability: empirical evidence from the banking sector in Bangladesh - Julia, Taslima; Kassim, Salina (IIUM Press, 2016)
Green financing is a relatively new phenomenon in Bangladesh’s banking sector following its introduction in 2011 by the Central Bank of Bangladesh. All 56 schedule banks in Bangladesh are required to adopt the green financing policies as part of the effort to promote environmentally friendly practices in their banking operations. The majority of these banks showed eagerness to set up their own green banking guidelines and green unit on time, although the seriousness to implement all the sections of the policy vary, indicating further motivation is needed to ensure actual implementation by all banks. Being a commercial entity motivated by profit, it would be interesting to investigate the relationship between green financing and profitability of the commercial banks. This paper aims to investigate the relation between profitability and green financing based on the experience of 30 sample banks in Bangladesh. Several profitability ratios, namely ROE, ROA, AU and ROD have been used to find the relation with green financing utilized funds for three years 2012, 2013 and 2014. The study finds that there are significant relationships among different banks of Bangladesh such as conventional commercial banks, Islamic commercial banks, state-owned commercial banks and foreign commercial banks in terms of profitability ratios. In particular, the ROA, ROD and AU have significant positive relationships with green financing of the banks, while the ROE showed no significant relationship with green financing of the banks.